2007
DOI: 10.1016/j.jbankfin.2007.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Daily mutual fund flows and redemption policies

Abstract: We examine how redemption policies affect daily fund flows in open-end mutual funds. Since short-term trading of fund shares, as manifested in daily fund flows, can have an adverse impact on returns to the fund's shareholders, mutual funds might find it desirable to discourage shortterm trading through the use of redemption fees. However, if daily fund flows are due to fund shareholders' legitimate liquidity demands, the redemption fee would have little effect on daily fund flows and possibly adversely affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Their results is consistent with Greene et al (2007), who found that even a redemption fee has no significant adverse impact on fund returns, it can be used to efficiently control the volatility of fund flow. Reconcile these findings, we propose that the behavioral bias of stock investment is pronounced under outflow condition, and there is asymmetric effect on asset allocation and trading behavior of fund manager for inflow and outflow fund portfolio.…”
Section: The Relationship Between Fund Flow On Trading Behaviorsupporting
confidence: 88%
“…Their results is consistent with Greene et al (2007), who found that even a redemption fee has no significant adverse impact on fund returns, it can be used to efficiently control the volatility of fund flow. Reconcile these findings, we propose that the behavioral bias of stock investment is pronounced under outflow condition, and there is asymmetric effect on asset allocation and trading behavior of fund manager for inflow and outflow fund portfolio.…”
Section: The Relationship Between Fund Flow On Trading Behaviorsupporting
confidence: 88%
“…Even so, Friesen and Sapp (2007) demonstrate that returns chasing behavior is detrimental to active fund traders' performance. Recently, the SEC has encouraged mutual funds to impose redemption fees on relatively short term traders, to compensate the remaining fund shareholders for the costs created by flow (Greene et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Our first measure is the fees that a fund charges its shareholders. Fund fees are at the center of the agency conflict between the fund management company and fund shareholders (Del Guercio et al, 2003;Bogle, 2005;Friesen and Sapp, 2007;Green et al, 2007;Cao et al, 2008). Higher fees enrich the fund management company, while eroding the net performance enjoyed by fund shareholders.…”
Section: Introductionmentioning
confidence: 99%